2019
DOI: 10.31219/osf.io/xfrve
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aging effects on neural entrainment to a musical beat

Abstract: When listening to music, the brain entrains to the musical rhythm and produces neural activity at the beat frequency. Younger (<35) and older (>60) adults listened to slow (1.25 Hz) and fast (2.5 Hz) syncopated and non-syncopated rhythms while intermittently performing a tapping task. EEG was recorded and frequency tagging was employed to analyze meter-related and meter-unrelated frequencies elicited by the rhythms. The meter-related frequencies included the beat frequency (BF), its first three h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Such variability in the efficacy of music-based interventions may arise, in part, from the diversity of protocols that underlie MBIs (e.g., self-selected vs. clinician-selected music), the heterogeneity of clinical populations that are targeted by MBIs, and individual differences in the sensitivity to musical features that constitute the intervention (e.g., rhythm, melody, motor-movement, and social interactions during musical experiences) (Loui, 2020; Sousa et al, 2020; Vink & Hanser, 2018). While research has identified key neural networks that contribute to music processing (Koelsch, 2014; Loui & Przysinda, 2017), little is known about the underlying neurobiological mechanisms that are specifically engaged by MBIs (Quinci et al, (2022); Wang et al, (2020)) and how aging affects neural responses to musical structure (e.g., rhythm, melody, harmony) (Sauvé et al, 2019; Sutcliffe et al, 2020). Yet, understanding how MBIs engage the nervous system and the impact of aging on the neural processing of music has important implications for designing and implementing MBIs; understanding naturalistic music-listening and -making on brain function, cognitive health, and well-being; and explaining individual outcomes following the intervention (Ferreri et al, 2019; Sutcliffe et al, 2020; Tichko et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such variability in the efficacy of music-based interventions may arise, in part, from the diversity of protocols that underlie MBIs (e.g., self-selected vs. clinician-selected music), the heterogeneity of clinical populations that are targeted by MBIs, and individual differences in the sensitivity to musical features that constitute the intervention (e.g., rhythm, melody, motor-movement, and social interactions during musical experiences) (Loui, 2020; Sousa et al, 2020; Vink & Hanser, 2018). While research has identified key neural networks that contribute to music processing (Koelsch, 2014; Loui & Przysinda, 2017), little is known about the underlying neurobiological mechanisms that are specifically engaged by MBIs (Quinci et al, (2022); Wang et al, (2020)) and how aging affects neural responses to musical structure (e.g., rhythm, melody, harmony) (Sauvé et al, 2019; Sutcliffe et al, 2020). Yet, understanding how MBIs engage the nervous system and the impact of aging on the neural processing of music has important implications for designing and implementing MBIs; understanding naturalistic music-listening and -making on brain function, cognitive health, and well-being; and explaining individual outcomes following the intervention (Ferreri et al, 2019; Sutcliffe et al, 2020; Tichko et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While music has been shown to entrain neural activity, impairments in neural en-trainment to musical features are associated with aging (Alain et al, 2014; Bones & Plack, 2015; Henry et al, 2017; Sauvé et al, 2019; Sutcliffe et al, 2020; Zendel & Alain, 2014). Relatedly, several neurodegenerative disorders, such as Mild Cognitive Impairment and Alzheimer’s Disease, are associated with disrupted neural activity across the same frequency bands that are driven by music (e.g., delta, theta) (Goodman et al, 2018; Güntekin & Başar, 2016; Hata et al, 2016; Koenig et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation